2011
DOI: 10.1186/1752-1947-5-239
|View full text |Cite
|
Sign up to set email alerts
|

Fibrous dysplasia of bone associated with soft-tissue myxomas as well as an intra-osseous myxoma in a woman with Mazabraud's syndrome: a case report

Abstract: IntroductionMazabraud's syndrome is a rare but well-described disorder characterized by fibrous dysplasia in single or multiple bones associated with one or more soft-tissue myxomas. In this report, we describe what is, to the best of our knowledge, the first case involving an intra-osseous myxoma. This finding supports, and could provide new insight into, the pathological association between fibrous dysplasia and myxomas.Case presentationIn this report, we describe the case of a 49-year-old Caucasian woman kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 14 publications
(14 reference statements)
1
19
0
Order By: Relevance
“…The fibrous dysplasia is associated with soft tissue myxomas that are located in the close vicinity of the bony lesion . The syndrome tends to occur more frequently in females than males . The development of fibrous dysplasia occurs early in life as described by our patient and it is reported that the intramuscular soft tissue myxomas occurs around the sixth decade of life and have a benign course .…”
supporting
confidence: 53%
See 1 more Smart Citation
“…The fibrous dysplasia is associated with soft tissue myxomas that are located in the close vicinity of the bony lesion . The syndrome tends to occur more frequently in females than males . The development of fibrous dysplasia occurs early in life as described by our patient and it is reported that the intramuscular soft tissue myxomas occurs around the sixth decade of life and have a benign course .…”
supporting
confidence: 53%
“…The syndrome tends to occur more frequently in females than males . The development of fibrous dysplasia occurs early in life as described by our patient and it is reported that the intramuscular soft tissue myxomas occurs around the sixth decade of life and have a benign course . They are considered soft tissue hamartomas with tumour‐like growth .…”
mentioning
confidence: 53%
“…The disease is more frequent in women than men and patients are often asymptomatic. However, complications such as skeletal deformities, fractures and pain can occur (1, 6, 7). The etiology of Mazabraud's syndrome is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Soft tissue myxomas are benign mesenchymal tumors, and fibrous dysplasia is a benign, intra-medullary, fibro-osseous lesion (1). The first case of Mazabraud's syndrome was described by Henschen (2) in 1926, and a pattern of association between fibrous dysplasia and soft tissue myxomas was presented by Mazabraud et al .…”
mentioning
confidence: 99%
“…Fibrous dysplasia developed in bone is a benign and fibro osseous lesion, and myxomas presented as benign mesenchymal tumors 1. The first case was reported by Mazabraud,23 which was finally named after his name.…”
Section: Introductionmentioning
confidence: 99%